PENGARUH KOMPLEKSITAS TUGAS, PENGALAMAN AUDITOR, SKEPTISME DAN TEKANAN ANGGARAN WAKTU TERHADAP AUDIT JUDGMENT: (Studi Kasus Kantor Akuntan Publik di Bali) - Hesdyana Tibe; Ni Nyoman Sri Rahayu T. Dewi (Universitas Triatma Mulya, 2020)
This study aims to determine the factors that influence audit judgment of the Public Accounting Firm (KAP) in Bali. These factors include task complexity, auditor experience, skepticism, and time budget pressure. The research method used in this study is quantitative. Respondents in this study were auditors working in Public Accounting Firms in Bali who had at least 1 (one) year experience using Purposive sampling technique as a sample determination. The data analysis technique used is multiple linear regression analysis. The test result show that task complexity has a negative effect on audit judgment of KAP in Bali, However auditor experience, skepticism and time budget pressure have a positive influence on audit judgment in Bali. Complexity assignments, auditor experience, skepticism, and time budget pressure influence together or simultaneously on audit judgment of KAP in Bali.Keywords: audit judgment, task complexity, auditor experience, skepticism, and time budget pressure.